Amēkhaníē in Parmênides DK B 6.5 - Galgano, Nicola Stefano (Journal of Ancient Philosophy, 2016)
The paper examines closer the notion expressed by the word amēkhaníē in DK 6. 5. In his analysis of problematic of knowledge Parmenides alerts about amekhaníē of mortals, a word generally translated with `lack of resources` or ‘perplexity’, a kind of problem that drives the thinking astray. Scholars point out in many passages of the poem the opposition between imperfect mortals and the eidóta phōta of DK 1. 3, the wise man. However, as much as I know, nobody noticed that, if mortals have a lack of resources, the goddess is teaching exactly how to fix it with a kind of method given through her precepts, which are an authentic mēchané. The paper shows that this is the genuine didactic aim of Parmenides, as he says in 1.28-30, i.e., to point out where is the error of mortals and how the wise man fixes it. Starting from a reinterpretation of 1.29 and following with the analysis of fr. 6, the paper shows that the method of fr. 2 is indeed the mēchané that can do that. Although the word is not present in the poem, it is one of its main topics. It seems (by the extant fragments) Parmenides had no clear word to call his mēchané, a psychological cognitive tool we call today principle of non-contradiction.